2012
DOI: 10.2164/jandrol.111.013367
|View full text |Cite
|
Sign up to set email alerts
|

Daily Use of Sildenafil Improves Endothelial Function in Men With Type 2 Diabetes

Abstract: Diminished vascular endothelial function results in decreased vasodilator capacity and is associated with erectile dysfunction (ED) in patients afflicted with type 2 diabetes. The current study was designed to evaluate whether daily use of sildenafil could alter endothelial function and improve penile rigidity in a group of patients with diabetic ED. A double-blind, placebo-controlled, prospective trial was conducted with 24 men with type 2 diabetes who were randomized into 2 groups: one receiving daily silden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 26 publications
1
28
0
1
Order By: Relevance
“…Data from the literature demonstrate an FMD improvement after chronic (13,24,25,26,27) and acute sildenafil administration in diabetic men (28). By using vardenafil, here, we demonstrate that FMD improves during treatment.…”
Section: Discussionsupporting
confidence: 62%
“…Data from the literature demonstrate an FMD improvement after chronic (13,24,25,26,27) and acute sildenafil administration in diabetic men (28). By using vardenafil, here, we demonstrate that FMD improves during treatment.…”
Section: Discussionsupporting
confidence: 62%
“…All trials were thoroughly appraised for their eligibility in the metaanalysis and their methodological quality. Six studies met the inclusion criteria (29,30,35,36,37,38) (Table 1). Ten studies were excluded from the final analysis as they did not fulfill inclusion criteria.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…All trials included in the meta-analysis (29,30,35,36,37,38) enrolled men with T2DM based on the definition of WHO (49). T2DM was defined in the same way in the six included studies, but a different duration of the disease was reported in the inclusion criteria of each RCT ( Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…В пользу применения ингибиторов ФДЭ-5 (иФДЭ-5) при СД говорят также, результаты двой-ного слепого плацебо-контролируемого исследова-ния [12], в котором была показана высокая эффек-тивность курсового применения силденафила для улучшения эректильной функции пациентов. Уста-новлено также улучшение NO-синтетической ак-тивности эндотелиоцитов в условиях инсулиноре-зистентности у больных с СД [13].…”
Section: сведения об авторахunclassified